2002
DOI: 10.1002/rcm.831
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residue specific stable isotope labeling for quantitative proteomics

Abstract: Various stable isotope labeling (SIL) techniques have recently emerged to improve the efficiency and accuracy of protein quantitation by mass spectrometry (MS). We have developed a mass-tagging strategy to incorporate stable isotope tagged amino acids into cellular proteins in a residue-specific manner during cell growth. In this study, we further extend this residue-specific SIL approach to the accurate quantitation of protein abundances in different cell populations. For proteins whose expression levels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
266
4
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(274 citation statements)
references
References 28 publications
3
266
4
1
Order By: Relevance
“…Quantitation methods differ at the level in which the label is introduced into the sample. Some techniques introduce the label in viable cells in cell culture ( 14 N/ 15 N labeling [122] and stable isotope labeling by amino acids in cell culture, SILAC [123,124]). Others introduce the tag at the protein level (isotope-coded affinity tags, ICAT [125]) or peptide level (isobaric peptide tags for relative and absolute quantifi-cation, iTRAQ [126] or 18 O-labeling during tryptic digestion [127]), whereas yet others use a label-free strategy in which quantitative information is extracted from LC-MS (extracted ion current, XIC) or MS/MS data (protein abundance index, PAI) in sequential experiments [128][129][130].…”
Section: Quantitation Strategies For Phosphoproteomic Studiesmentioning
confidence: 99%
“…Quantitation methods differ at the level in which the label is introduced into the sample. Some techniques introduce the label in viable cells in cell culture ( 14 N/ 15 N labeling [122] and stable isotope labeling by amino acids in cell culture, SILAC [123,124]). Others introduce the tag at the protein level (isotope-coded affinity tags, ICAT [125]) or peptide level (isobaric peptide tags for relative and absolute quantifi-cation, iTRAQ [126] or 18 O-labeling during tryptic digestion [127]), whereas yet others use a label-free strategy in which quantitative information is extracted from LC-MS (extracted ion current, XIC) or MS/MS data (protein abundance index, PAI) in sequential experiments [128][129][130].…”
Section: Quantitation Strategies For Phosphoproteomic Studiesmentioning
confidence: 99%
“…We have previously shown that stable isotope-labeled amino acids can be naturally incorporated into cellular proteomes through cell culturing in a residue-specific manner (19). Subsequently, both our group and the group of Mann and colleagues (20,21) independently applied stable isotope labeling for quantitative protein profiling. In the current study, we combined stable isotope labeling and epitope tagging to allow the sensitive and selective identification of the MyD88-signaling complex formed in actual immune cells.…”
mentioning
confidence: 99%
“…Stable isotope labeling by amino acids in cell culture (SILAC) represents a simple and accurate method to explore expression proteomics in cell culture. [8][9][10][11] This methodology described by Ong et al 12 enables the identification of functional expression of proteins by administration to the culture medium of nonradioactive isotope labeled essential amino acids that are incorporated into all newly synthesized proteins. In our study, we have analyzed and compared the secreted proteome-profiling of cultured chondrocytes and cartilage explants by using a stable isotope labeling strategy in combination with 1D SDS-PAGE protein fractionation (shotgun), in-gel digestion, and LC/MS-MS analysis.…”
mentioning
confidence: 99%